Time series of hospitalizations of adolescents due to mental and behavioral disorders - Ellen Vanuza Martins Bertelli; Rosana Rosseto de Oliveira; Marcia Lorena Alves dos Santos; Eniuce Menezes Souza; Carlos Alexandre Molena Fernandes; Ieda Harumi Higarashi
ABSTRACT Objective: to analyze the trend of hospitalizations of adolescents due to mental and behavioral disorders in Paraná, from 1998 to 2015. Method: ecological study of time series. Data were analyzed by means of segmented linear regression modeling for time series, estimated for each of the four health macro-regions. Results: the East macro-region showed a greater trend to increase hospitalizations from January 1998 to November 2003 (β1=0.006, p<0.001). In other macro-regions, there were similar trends with a sudden increase in February 2010, but with a further gradual decrease until December 2015. In the quadrennium 2012-2015, 38.06% of the hospitalizations lasted 29 or more days, and in the Northwest macro-region, hospitalizations lasted for up to seven days. The main cause of hospitalization was the use of alcohol and other drugs. Conclusion: there is a need to strengthen health actions to prevent drug use and improvements in the care network.